2012
DOI: 10.1590/s0103-51502012000300007
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre os desempenhos em diferentes testes frequentemente utilizados na avaliação da função manual

Abstract: Fisioter Mov. 2012 jul/set;25(3):517-24 Lima KCA, Francisco MM, de Freitas PB. 518 seus resultados devem ser utilizados com cautela, pois essa variável não contempla todos os aspectos que envolvem a coordenação e o controle das forças atuantes durante a manipulação de objetos. Os testes 9-PnB e TFMJT indicam características diferentes relacionadas às capacidades manipulativas. [P] Palavras-chave: Função manual. Destreza. Dinamômetro de força muscular. [K]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
3
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 25 publications
1
6
3
5
Order By: Relevance
“…In addition, no difference between muscle strength and manual dexterity variables for the dominant and non-dominant upper limbs was observed. These results differ from those described in the literature, which has shown that the dominant member is able to develop higher levels of muscle strength and has a better performance on tasks that require manual dexterity in relation to the non-dominant member (Lima et al, 2012;Lima et al, 2011;Ozcan et al, 2004).…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…In addition, no difference between muscle strength and manual dexterity variables for the dominant and non-dominant upper limbs was observed. These results differ from those described in the literature, which has shown that the dominant member is able to develop higher levels of muscle strength and has a better performance on tasks that require manual dexterity in relation to the non-dominant member (Lima et al, 2012;Lima et al, 2011;Ozcan et al, 2004).…”
Section: Discussioncontrasting
confidence: 90%
“…In those tasks, better performance of the dominant upper limb has been observed (Lima et al, 2012;Lima, Santos, & de Freitas, 2011;Ozcan et al, 2004). The association between strength and dexterity in aiming movement performance of the right and left sides was not examined in these studies.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…O déficit funcional da mão é uma das sequelas mais significativas no indivíduo hemiparético, visto que a mão tem um papel importante no plano de independência e de autoestima desses indivíduos. Assim, é interessante que ele utilize o membro superior acometido, mesmo que este tenha pouca ou nenhuma preensão 15 .…”
Section: Discussionunclassified
“…Recent studies have found that the HGSMax, when performed by young, healthy adults, had no relationship with digits dexterity, as measured by the performance on the Nine Hole Peg Test (9-HPT) (25), and a moderate relationship with manual dexterity or overall hand function, as evaluated by the JebsenTaylor Hand Function Test (JTHFT) (26). Based on these studies it is possible to suggest that using only the HGSMax test would not be sufficient to describe upper limb function.…”
Section: Introductionmentioning
confidence: 99%